An Innovative Approach with [68Ga]Ga-PSMA PET/CT: The Relationship Between PRIMARY Scores and Clinical and Histopathological Findings - Gozde Mutevelizade; Bilal Cagri Bozdemir; Nazim Aydin; Elvan Sayit (Diagnostics)
Background/Objectives: The aim of this study was to investigate the relationship between the PRIMARY score derived from [68Ga]Ga-PSMA PET/CT and key clinical and pathological parameters of prostate cancer aggressiveness, including the PSA level, ISUP Grade Group, and D’Amico risk classification, in patients with biopsy-proven prostate cancer. A secondary aim was to evaluate the interobserver agreement of the PRIMARY score in routine clinical practice. Methods: This retrospective analysis included 51 patients with histopathologically confirmed prostate adenocarcinoma who underwent [68Ga]Ga-PSMA PET/CT imaging for staging. PRIMARY scores were determined based on the intraprostatic uptake pattern, intensity, and zonal localization. These scores were compared with PSA levels, ISUP GG, D’Amico risk classification, and histopathological features such as the cribriform pattern, intraductal carcinoma, perineural invasion, extraprostatic extension, and lymphovascular invasion. The PRIMARY scores were independently assigned by a total of three nuclear medicine physicians, and interobserver agreement was calculated using Fleiss’ kappa analysis. Results: Significant associations were found between the PRIMARY scores and the PSA level, ISUP Grade Group, and D’Amico risk classification. The most prevalent score was PRIMARY 5 (54.9%), which was significantly associated with ISUP GG 5 and the high-risk category in D’Amico classification. Among patients with PRIMARY Score 2, a substantial proportion (64.7%) had ISUP GG ≥ 3, and 58.8% were in the high-risk group, highlighting the limitations of binary PRIMARY classification. No statistically significant correlations were found between the PRIMARY scores and specific histopathologic features. Interobserver agreement was excellent (κ = 0.833). Conclusions: The PRIMARY score demonstrates high reproducibility and clinical relevance in stratifying prostate cancer aggressiveness. However, the findings challenge the reliability of binary classifications, particularly for patients with Score 2, who may still harbor high-grade disease. Integrating imaging-based scores with clinical and histopathological data is essential, particularly for accurate staging and decision-making regarding active surveillance.